THE ROLE OF DIGITAL MARKETING AND SERVICE QUALITY ON CUSTOMER LOYALTY IN THE CAFE BUSINESS AT KAVLING DPR SIDOARJO THROUGH CUSTOMER ENGAGEMENT AS MEDIATION - Rafli Permana Putra; Muhammad Yani; Kumara Adji Kusuma (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the influence of digital marketing and service quality on customer loyalty through customer engagement in cafe businesses in the Kavling DPR Sidoarjo area. Method: The study used a quantitative approach with a purposive sampling technique on 114 respondents who had visited and interacted with digital cafe media in the area. Data analysis was conducted using the Partial Least Squares (PLS) method. Results: The results showed that digital marketing and service quality had a positive and significant effect on customer engagement, while customer engagement had a positive and significant effect on customer loyalty. Service quality was also proven to have a positive and significant effect on customer loyalty, while digital marketing had a significant negative effect on customer loyalty. In addition, customer engagement was able to significantly mediate the effect of digital marketing on customer loyalty, but was not able to mediate the effect of service quality on customer loyalty. Novelty: The research findings indicate that consistent service quality and interactive, relevant, and moderate digital marketing strategies are important factors in increasing customer engagement and loyalty in cafe businesses. The implications of this study emphasize the importance of cafe businesses to optimize service quality, strengthen creative and personalized digital communication, and build long-term relationships with customers through increased customer engagement to face increasingly competitive F&B businesses.